Perbandingan Kualitas Terjemahan Dua Karya Terjemahan Cerpen Jalan Lain ke Roma Karya Idrus Ditinjau dari Pengembangan Tema - Sukma, Bayu Permana; Efse, Herlina Astuti (Kementerian Sekretariat Negara Republik Indonesia, 2018)
Systemic Functional Linguistics provides many resources for translation studies. Some translation scholars even explicitly suggested SFL approach to develop their theories. One of SFL key features which can be applied to measure translation quality is thematic structure. This is possible because a good text should be composed of cohesive clauses (Eggins, 1994; Emilia, 2011). While theme has widely become topics in research on translations from other languages into English, it is still rarely explored in bahasa Indonesia-English translation. Using Eggins’ (2004) model of thematic progression, the authors explored how this feature was used in two English versions of Indonesian short story Jalan Lain ke Roma. Through the analysis and the comparison of thematic progression in source text and the two target texts, the authors attempted to show which text is better based on the thematic choices. The result of this study shows that although there is not significant difference between the two versions, the text titled Another Road to Rome is better at cohesion than the other titled Another Way to Rome. Keywords: Systemic Functional Linguistics, thematic structure, thematic progression, translation quality